The Impact of Out-of-Pocket Health Expenditure and Public Health Expenditure on Poverty in Sub-Saharan Africa - Tewa Papy Voto; Bangapa Emery Voto; Nicholas Ngepah (Economies)
The modern world is confronting interconnected challenges, such as achieving sustainable health system financing for poverty reduction, amid limited guidance for stakeholders. Adhering to SDG-3 guidelines for good health and well-being could aid in accomplishing SDG-1 for eradicating poverty. This roadmap requires scientific validation. Therefore, this study aims to investigate the effect of out-of-pocket health expenditure (OOPHE) and government health expenditure (GHE) on poverty in sub-Saharan Africa (SSA) using Fully Modified Ordinary Least Squares (FMOLS) from 1990 to 2022. The results reveal that OOPHE increases poverty in the long run. In addition, the results also show that GHE augments poverty in the long run. Moreover, it is observed that GHE reinforces the positive impact of OOPHE on poverty in the long run. Additionally, the study’s empirical results support the conclusion that policymakers should advocate for the effective management of government health expenditure.